2016
DOI: 10.1017/hpl.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high-quality electron beams by ionization injection in a single acceleration stage

Abstract: Ionization-induced electron injection in laser wakefield accelerators, which was recently proposed to lower the laser intensity threshold for electron trapping into the wake wave, has the drawback of generating electron beams with large and continuous energy spreads, severely limiting their future applications. Complex target designs based on separating the electron trapping and acceleration stages were proposed as the only way for getting small energy-spread electron beams. Here, based on the self-truncated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…( ) [20,22,43], where the normalized transverse momentum p is estimated to be the normalized laser vector at the ionization position, i.e. p=1.9, and the Lorentz factor γ 0 of the wake phase velocity at the gas density of 2.75×10 18 cm −3 is estimated by the linear theory g w w = =18, 0 p as the dotted black line shown in figure 6(a).…”
Section: D-pic Simulations and Discussionmentioning
confidence: 99%
“…( ) [20,22,43], where the normalized transverse momentum p is estimated to be the normalized laser vector at the ionization position, i.e. p=1.9, and the Lorentz factor γ 0 of the wake phase velocity at the gas density of 2.75×10 18 cm −3 is estimated by the linear theory g w w = =18, 0 p as the dotted black line shown in figure 6(a).…”
Section: D-pic Simulations and Discussionmentioning
confidence: 99%
“…As a result, the final electron energy spread is largely reduced. It is called self-truncated ionization injection (Zeng et al 2014), which was demonstrated experimentally in Shanghai Jiao Tong University (Mirzaie et al 2015;Hafz et al 2016). In the second scheme, using two laser pulses with fundamental frequency and high harmonics co-propagating in a gas target, ionization injection can be further controlled by proper choice of the two laser field amplitudes.…”
Section: Laser Plasma-based Electron Accelerationmentioning
confidence: 99%
“…In 2014, Yu et al [2] and Xu et al [3] proposed employing two laser pulses of different wavelengths in the generation of low-emittance electron beams, respectively. In such a scheme, a long-wavelength (mid-infrared) laser pulse, with a large ponderomotive force and small peak electric field, was used to excite a large plasma wake while a copropagating or transverse-colliding, time-delayed, and short-wavelength intense laser pulse was employed to trigger ionization injection [4][5][6][7][8][9][10] of electrons from the inner-shell high-Z ions (such as krypton, nitrogen, carbon or oxygen) inside the wake. The short-wavelength laser pulse can produce electrons with small residual momenta (p ⊥ ∼ a 0 ∼ √ Iλ) inside the wake, leading to electron beams with small normalized emittances.…”
Section: Introductionmentioning
confidence: 99%